(untitled) (Training and Practice : Journal of Educational Sciences, 2008)
This study is a theoretical summary of attachment theory with some possible applications in teaching and rearing children. Bowlby formulated his ideas as a theory of personality development, so it can be applied beyond infancy as well. Developmental aspects are highlighted and some former empirical evidence is presented about the connection between attachment theory and academic achievment and it’s relevance with school behavior and adjustment. Four different practical applications are concluded: (1) personality of the teacher as part of optimal learning environment; (2) attachment’s effect on teacher-student dialogue; (3) teacher-student relation as emotionally corrective experience; (4) education of boarding house students.